INfluenza Vaccine Indication During therapy with Immune checkpoint inhibitors: a multicenter prospective observational study (INVIDIa-2). Issue 5 (20th May 2021) - Bersanelli, Melissa; Giannarelli, Diana; De Giorgi, Ugo; Pignata, Sandro; Di Maio, Massimo; Clemente, Alberto; Verzoni, Elena; Giusti, Raffaele; Di Napoli, Marilena; Aprile, Giuseppe; Ermacora, Paola; Catino, Annamaria; et al.
Abstract : Background: Until now, no robust data supported the efficacy, safety and recommendation for influenza vaccination in patients with cancer receiving immune checkpoint inhibitors (ICIs). Methods: The prospective multicenter observational INfluenza Vaccine Indication During therapy with Immune checkpoint inhibitors (INVIDIa-2) study investigated the clinical effectiveness of influenza vaccination in patients with advanced cancer receiving ICIs, enrolled in 82 Italian centers from October 2019 to January 2020. The primary endpoint was the time-adjusted incidence of influenza-like illness (ILI) until April 30, 2020. Secondary endpoints regarded ILI severity and vaccine safety. Results: The study enrolled 1279 patients; 1188 patients were evaluable for the primary endpoint analysis. Of them, 48.9% (581) received influenza vaccination. The overall ILI incidence was 8.2% (98 patients). Vaccinated patients were significantly more frequently elderly (p<0.0001), males (p=0.004), with poor European Cooperative Oncology Group performance status (p=0.009), affected by lung cancer (p=0.01), and by other non-cancer comorbidities (p<0.0001) when compared with unvaccinated. ILI incidence was not different basing on influenza vaccination: the time-to-ILI was similar in vaccinated and unvaccinated patients (p=0.62). ILI complications were significantly less frequent for patients receiving the vaccination (11.8% vs 38.3% in unvaccinated, p=0.002). ILI-related intravenous therapies were significantly less frequent in vaccinated patients than in unvaccinated (11.8% vs 29.8%, p=0.027). ILI lethality was, respectively, 0% in vaccinated and 4.3% in unvaccinated patients. Vaccine-related adverse events were rare and mild (1.5%, grades 1–2). Conclusion: The INVIDIa-2 study results support a positive recommendation for influenza vaccination in patients with advanced cancer receiving immunotherapy.